Combination of Nicorandil and Beta-Adrenergic Receptor Blockers in Patients with Coronary Artery Disease: A Real-World Observational Study - Jia Cheng MD, PhD; Lin Qiu MS; Zixuan Zhang MD; Na Li MD; Hongyang Shu MD, PhD; Zhichao Xiao MD, PhD; Ning Zhou MD, PhD (SAGE Publishing, 2023)
Background The effect of combined nicorandil and beta-adrenergic receptor blockers (BBs) compared with that of BBs alone on long-term clinical outcomes in patients with coronary artery disease (CAD) remains undetermined. Methods A multicenter retrospective cohort study was performed. Adult patients who had been hospitalized for CAD and treated for angina with a combination of nicorandil and BBs or BBs alone were included. The effect of different treatments on the cumulative incidence of major adverse cardiovascular event (MACE) and their components within a follow-up duration of 2.5 years were analyzed using Kaplan-Meier survival curves. An inverse probability of treatment weighting (IPTW) method was used to adjust for the possible effect of confounding factors. Results A total of 137,714 patients were screened, of whom 16,912 individuals (mean age: 61.5 years, men: 67.1%) were successfully enrolled. Among the enrolled participants, 4669 received the combined treatment of nicorandil and BBs, while 12,243 received BBs alone. After IPTW, the results demonstrated that the combined treatment was associated with a significantly reduced incidence of MACE (hazard ratio [HR] 0.79, 95% conidence interval [CI] 0.72-0.87) and stroke (HR 0.48, 95% CI 0.42-0.54) but not of MI (HR 1.03, 95% CI 0.92-1.15) or all-cause mortality (HR 0.93, 95% CI 0.64-1.37). Sensitivity analyses revealed similar results. Conclusions A combined antiangina treatment of nicorandil and BBs may be more effective than treatment of BBs alone in reducing the long-term incidence of MACE in patients with CAD.